IoT-based Stunting Education and Early Detection System for Stunting-Free Indonesia - Listiarini Edy Sudiati; Wahyu Aditama; Daniel Alfa Puryono (East Asian Journal of Multidisciplinary Research, 2023)
Indonesia's stunting prevalence 2022 reached 21.6%, which is still high compared to the WHO threshold of 20%. The Indonesian government's target for 2023 is 17% and the target for 2024 is 14%. Stunting is a long-term chronic nutritional condition that disrupts children's growth. In line with the government program, this research was conducted to build an education system & early detection of stunted children using IoT technology. The target users of the system are prospective brides, pregnant women, postpartum mothers and PKK cadres. With the education system and early detection of stunting children, it is hoped that brides-to-be, pregnant women, and postpartum mothers can understand how to prevent stunting babies, and make it easier for users to communicate, consult about stunting babies so that they can reduce the prevalence of stunting according to government targets. The research method used is the classic software development model, which is waterfall.